2022
DOI: 10.1182/bloodadvances.2021006844
|View full text |Cite
|
Sign up to set email alerts
|

An international analysis evaluating frontline bendamustine with rituximab in extranodal marginal zone lymphoma

Abstract: Extranodal marginal zone lymphoma (EMZL) is a heterogeneous non-Hodgkin lymphoma. No consensus exists regarding the standard-of-care in patients with advanced-stage disease. Current recommendations are largely adapted from follicular lymphoma for which bendamustine with rituximab (BR) is an established approach. We analyzed the safety and efficacy of frontline BR in EMZL using a large international consortium. We included 237 patients with a median age of 63 years (range 21 to 85). Most patients presented with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 43 publications
4
16
0
Order By: Relevance
“…In 235 patients with Waldenstroem's Macroglobulinemia treated with BR induction, 89.9% of patients achieved a PR 21 . Treatment with BR demonstrated excellent efficacy in our MZL patients with 100% ORR, similar to the previously reported rate between 89.3 to 100% 19,22 . CR rate was similar for elderly and younger patients.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In 235 patients with Waldenstroem's Macroglobulinemia treated with BR induction, 89.9% of patients achieved a PR 21 . Treatment with BR demonstrated excellent efficacy in our MZL patients with 100% ORR, similar to the previously reported rate between 89.3 to 100% 19,22 . CR rate was similar for elderly and younger patients.…”
Section: Discussionsupporting
confidence: 86%
“…The proportion of patients who experienced fatigue was not increased in the elderly group. The rate of infections in our patients was similar to the one reported in STiL and BRIGHT trials but was higher than in a recent multicenter report of BR in extranodal MZL where 13% of patients experienced infectious complications during BR therapy, including herpes zoster reactivation in 4% of patients 19 . In our patients, herpes zoster reactivation was significantly higher in the elderly cohort; thus, we now introduced prophylactic treatment with valacyclovir at our institution.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Lymphopenia was the most frequently observed adverse event [ 112 ]. Further studies have confirmed these findings [ 113 , 114 , 115 ], also in pretreated patients [ 116 ]. Of note, one large study of an international consortium with 237 EMZL patients showed an ORR of 93.2% and a CR rate of 80%.…”
Section: Therapymentioning
confidence: 58%
“…Patients received a median of six cycles (range 1–8). Importantly, treatment with bendamustine is related to prolonged lymphopenia and risk of infections; Herpes zoster was frequently observed in patients treated with this regimen, and therefore, an adequate prophylaxis might be needed until immune reconstitution [ 114 ].…”
Section: Therapymentioning
confidence: 99%